Epilepsia"Petit Mal" aspectos clínicos, eletrencefalográficos e evolutivos - Paulo Pinto Pupo; Olavo Pazzanese; Rosa Helena Longo (Arquivos de Neuro-Psiquiatria)
In the past few years somewhat new yet often differing points of view have been affirmed refering to Petit Mal epilepsy, with regard to its clinical, eletrencephalographic and evolutive aspects. The classical concept of PM epilepsy as established by Lennox and Gibbs, with its well defined clinical and EEGraphic characteristics is continually being modified with new research work on clinical and EEGraphic aspects. Numerous clinical cases have been published whose evolution clashes with that classically described and likewise numerous are those cases where the EEG shows signs of focal electric activity besides spike and wave dis-rythmia. Cases have been known where surgical exerese on the focus causes temporary desappearance of the spike and wave disrythmia. The present concept now holding sway is that PM epilepsy is a kind of reaction of infantile encephalon to diverse harmful causes. From this it will be seen we are very far from the concept that PM epilepsy is a pure form of idiopathic epilepsy. For these reasons we decided to re-examine those cases observed between 1950 and 1960. With this in mind we chose 141 PM epilepsy cases, from among over 23000 epileptics, all examined under a standard criterion by a small group of senior assistants. All cases suspected of Psm epilepsy were excluded. The analysis of this group of patients was compared to that of another group with GM as well as PM seizures (104 patients); in 52 of these cases, studies were made concerning the evolutive, clinical and EEGra-phic aspects. METHOD: Clinical criterion was used for selection of the cases. The results of the analysis from the clinical and EEGraphic point of view were exhibited in demonstrative graphs. From the clinical point of view we strove to find out positive hereditary elements, organic cerebral injury factor (intellectual deficit, mood and behaviour disturbances, neurologic or somatic signs, as well as other development anomalies), the presence of febrile convulsions before the setting in of clinical PM syndrome and the eventuality of abnormal birth. We listed the patients according to their sex and investigated the statement that there is a prevalence of PM seizures among women. We attempted to analyse the incidence of cases according to the patient's age, as well as the incidence regarding the onset age of the illness. With regard to the EEG we likewise attempted to analyse those elements enabling us to weigh up the lesional factors in the brain (abnormalities in the background activity, disrythmias with focal characteristics or other paroxysmal abnormalities of a lesional type) and the bilateral and synchronous paroxysmal disrythmias classically known as forming part of the Petit Mal epileptic picture. Out the group of patients presenting pure PM seizures (141 cases) we obtained a clinical and EEGraphic sequence in 37, during a period of time ranging from 1 to 13 years. Of the group of patients presenting GM seizures as well as PM (104 patients) we investigated, in a comparative manner, 15 cases in a cliincal and EEGraphic sequence, during a period ranging from 1 to 9 years. RESULTS: The analysis of the clinical and electroencephalographic aspects in the first group of patients (141 cases with PM seizures) has enabled us to point out - a) A greater occurrence of this disease between the ages 6 and 12 - though there were 48 patients between the ages of 11 and 20 and 16 patients above 20 years old; b) in the majority of cases the disease set in between the age of 6 and 10 (47 cases); in some cases however the disease started up under two years of age; in 31 patients the onset was after 11 years of age; c) as far as sex distribution, there was no significant difference; d) barely 1 case proved to be abnormal in the somatic examination congenital cardiopathy) ; e) the occurrence of psychic disturbances among patients was extremely low; f) there were no cases with past history of abnormal birth; g) back-ground activity was with in the limits of normality in the great majority of cases; h) incidence of bilateral and synchronous spike and wave 3 c/s, was fairly high; slower disrythmia of this type was present in 4 cases only; i) larval disrythmias by spikes or multiple-spikes and slow ware occurred quite often and appeared both in the mioclonic form of PM as well as in the other forms of the disease; j) diffuse and irregular slow sharp waves, were found in 7 patients and sharp focal waves in 4; these alterations would always seem to appear associated with bilateral and synchronous disrythmias. The analysis of these same elements in the second group (104 patients with PM plus GM seizures) has enabled us to note the following details: a) later age of onset; b) in 5 cases there was child-birth asphyxia; c) higher incidence of cases presenting bilateral and synchronous disrythmias with a frequency below 3 c/s. The development aspects of our patients was not uninteresting. Out of 37 patients with pure PM seizures we noted: a) that the age of onset did not on the whole favour or unfavour the evolution; b) the great majority of cases developed favorably: 18 patients have no more seizures, 11 still present a very minimum number of seizures; 6 later had GM seizures associated; one patient showed a rather serious impairment of his seizures; c) in cases of favorable development,' synchronous disrythmias by spike and wave 3 c/s disappeared, which was not what happened in the group of cases showing unfavorable development; d) total disappearance of disrythmias was only noted in those cases of favorable development; e) there were cases, both among the favorable and unfavorable development groups, where the initial disrythmias perceptibly modified with time and became diffuse sharp waves; f) background activity was normal in the great majority of cases; g) some of our patients developed with clinical fits even over the age of 30. Out of 15 patients with GM plus PM seizures and on whom development studies were made, we noted that the results differed very little from those of the previous group. We should like to point out, however, that disappearance of the spike and wave 3 c/s disrythmias did not occur, even in those cases presenting favorable clinical development. COMMENTS: After discussing the most interesting facts stated in the analysis of their cases and co-relating them to litterature data found, with particular reference to the works presented at the Congress of Brussels by Jung, Bickford, Droogleever-Fortuyn, Gibbs and Walker, the AA have come to the following conclusions: 1) there are clinical and electroence-phalographic indications that the syndrome "Petit Mal Epilepsy" is a clinical manifestation of diverse brain affections; 2) the starting up of the Petit Mal syndrome occurred at an age below 11 years in the majority of cases; however, there are others where the onset occurred after this age and in some cases even above the age of 20; 3) the persistence of Petit Mal clinical syndrome with electroencephalographic manifestations of the complex spike and wave 3 c/s. type can occur in many patients after the age of 15 and up to the age of 40, which fact is in complete disaccord with the classical idea of Petit Mal epilepsy good prognosis after puberty.